The New Numerical Methods for Mathematical Modelling of Pollutant Transport - Kovarik, Karel (Communications - Scientific Letters of the University of Zilina, 1999)
This paper deals with a solution of the transport governing equation in the saturated zone by the random-walk and DR method connected with the boundary element method. The boundary element's solution produces a continuous velocity field which is used to solve the transport equation by both methods. These models can be effectively used to simulate groundwater contamination problems.
Keywords: no keywords